QUALITY OF LIFE OF PATIENTS WITH END-STOMA IN MEDAN: A PHENOMENOLOGICAL STUDY - Fahrizal Alwi; Setiawan Setiawan; Asrizal Asrizal (Belitung Nursing Journal, 2018)
Background: Colorectal cancer continues to be a serious problem in Indonesia. A common colorectal treatment is surgical removal of the diseased colon, followed by the creation of a colostomy through the abdominal wall to bypass the colorectal function of emptying waste products. Those who require permanent colostomy are likely to have quality of life issues impacting their physical, psychological, social, and spiritual needs. There issues impact persons’ life satisfaction, happiness, and overall quality of life. Objective: The aim of study was to describe the experiences of patients with end-stoma regarding their quality of life. Methods: The study design used descriptive phenomenology following the approach of Collaizzi. There were 12 participants who qualified using purposive sampling based on the inclusion criteria. The data were gathered in-depth interviews. Analysis and interpretation used verbatim descriptions in Bahasa Indonesia and subsequently translated into English language. Results: The research emerged seven themes, namely: (i) becoming limited in doing daily activity, (ii) having limitation during sexual and social intercourse, (iii) having various negative feelings after the existence of end-stoma, (iv) having financial difficulties, (v) attempting to survive with end-stoma, (vi) experiencing changes in fulfilling rest and sleep, physic, and complication, and (vii) having expectation which has to be achieved after having end-stoma. Conclusion: The results show that patients with end-stoma run into spiritual, social, psychological and physical disorder that affect the quality of their life. This study provides an understanding of the quality of life of patients with end-stoma and nurses are able to provide appropriate nursing care.